2007
DOI: 10.1136/qshc.2006.019828
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient communication about medication use at the interface between hospital and primary care

Abstract: Background: Lack of updated and uniform medication lists poses a problem for the continuity in patient care. The aim of this study was to estimate whether hospitals succeed in making accurate medication lists congruent with patients' actual medication use. Subsequently, the authors evaluated where errors were introduced and the possible implications of incongruent medication lists. Methods: Patients were visited within one week after discharge from surgical or medical department and interviewed about their use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
57
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 37 publications
8
57
0
3
Order By: Relevance
“…Investigation of the 471 relative contributions of the clinical pharmacist and NCHD 472 to the resolution of these non-reconciliations is a novel 473 aspect of this research and as such is not directly compa-474 rable to other studies in the field. 475 Substantial changes to patient's medications during their 476 inpatient stay and a clear absence of complete and accurate 477 information about many of these changes at discharge has 478 been demonstrated in this study, as is widely documented 479 in research literature [13,21,22]. Through review of dis-480 charge prescriptions, the clinical Pharmacist identified 481 prescription non-reconciliations on 62.5 % of prescriptions 482 and for 15.8 % of medications, and communication non-483 reconciliations on 92 % of prescriptions and for 45.8 % of 484 medications.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 76%
“…Investigation of the 471 relative contributions of the clinical pharmacist and NCHD 472 to the resolution of these non-reconciliations is a novel 473 aspect of this research and as such is not directly compa-474 rable to other studies in the field. 475 Substantial changes to patient's medications during their 476 inpatient stay and a clear absence of complete and accurate 477 information about many of these changes at discharge has 478 been demonstrated in this study, as is widely documented 479 in research literature [13,21,22]. Through review of dis-480 charge prescriptions, the clinical Pharmacist identified 481 prescription non-reconciliations on 62.5 % of prescriptions 482 and for 15.8 % of medications, and communication non-483 reconciliations on 92 % of prescriptions and for 45.8 % of 484 medications.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 76%
“…However, in Germany it is far from reality and difficult to put into practice. Besides improvement in communication between family and hospital doctors via transmission of more detailed information about drug changes to the discharge medication list (Clintborg et al 2007;Gonski et al 1993), perhaps more patient information, such as pharmaceutical counseling and better informing of patients concerning their pharmaceutical care plan, might be helpful to reduce posthospital drug prescribing (Al-Rashed et al 2002;Sorensen et al 2004). Furthermore, use of modern media like the world-wide web in primary care practices opens up new possibilities for better maintenance of adequate drug treatment after hospital discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Çeşitli hastalıkların artması ve yaşlanan nüfus ile birlikte, polifarmasi uygulamalarının da gittikçe arttığı ve reçete edilen ilaçlar hakkında hastaların yetersiz bilgiye sahip olması, sonucunda, istenmeyen yan etkilerin ortaya çıktığı bilinmektedir. Dolayısıyla, uygun olmayan ilaç kullanımını ve advers ilaç etkilerini önlemek için de eczacı hasta iletişimi önemlidir (43). Çalışmalar, hasta çıktılarında ve uyuncunda artışın, reçete edilen ilaç sayısında ve ilaçla ilgili problemlerin azalışının eczacı-hasta iletişiminin etkinliğinin rolü olduğunu göstermektedir (38).…”
Section: Kişisel Engellerunclassified